2017
DOI: 10.5455/aim.2017.25.163-168
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Para Clinical Information Needs of Infertility Electronic Health Records in Iran: A Delphi Study

Abstract: Background:infertility is referred to the person’s inability to conceive pregnancy after one year of intercourse without using protection. This study paves the ground for creating a complete, united, and coherent source of patients’ medical information.Materials and Methods:this is an applied research of descriptive-cross sectional type which has been carried out through qualitative – quantitative methods. The sample of the present study was 50 specialists in the field of infertility which has been chosen base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…This instrument consists of 5 domains of demographic data, medical history, paraclinical data, treatment plans, and treatment outcomes. The results of two studies (using the Delphi technique) on infertility registry data in Iran (29,30) revealed that most infertility experts agreed with the design of a tool for the infertility registry system that contained medical history, treatment plant, treatment outcome, and donor information domains, and the coefficient of the agreement was greater than 75%. These results are consistent with those of the current study.…”
Section: Discussionmentioning
confidence: 98%
“…This instrument consists of 5 domains of demographic data, medical history, paraclinical data, treatment plans, and treatment outcomes. The results of two studies (using the Delphi technique) on infertility registry data in Iran (29,30) revealed that most infertility experts agreed with the design of a tool for the infertility registry system that contained medical history, treatment plant, treatment outcome, and donor information domains, and the coefficient of the agreement was greater than 75%. These results are consistent with those of the current study.…”
Section: Discussionmentioning
confidence: 98%
“…in sources [20,[45][46][47]. and couples' treatments [45]. Another categorization divides these data into three main groups: the patient's main information, the previous medical history, and the treatment plan [47].…”
Section: Am J Biomed Sci and Resmentioning
confidence: 99%